1991
DOI: 10.1172/jci115220
|View full text |Cite
|
Sign up to set email alerts
|

Dr(a-) polymorphism of decay accelerating factor. Biochemical, functional, and molecular characterization and production of allele-specific transfectants.

Abstract: The Dr' antigen belongs to the Cromer-related blood group system, a series ofantigens on decay accelerating factor (DAF), a glycosyl-phosphatidylinositol-anchored membrane protein that protects host cells from complement-mediated damage. We studied the rare inherited Dr(a-) phenotype to ascertain the associated biochemical and functional changes in DAF and to characterize the basis for this polymorphism. Radioimmunoassay and flow cytometric analysis ofDr(a-) erythrocytes demonstrated 40% of normal surface expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…4). This shows that our previous finding (12) of a lack of reactivity of the Dr adhesin with Drb erythrocytes (that express only one-third the normal levels of DAF) was due to the absence of an adhesin binding site rather than to the lower expression of DAR The Dr' and Drb change does not appear to affect the complement regulatory function of DAF (30), so the adhesin and complement binding sites may not be the same.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…4). This shows that our previous finding (12) of a lack of reactivity of the Dr adhesin with Drb erythrocytes (that express only one-third the normal levels of DAF) was due to the absence of an adhesin binding site rather than to the lower expression of DAR The Dr' and Drb change does not appear to affect the complement regulatory function of DAF (30), so the adhesin and complement binding sites may not be the same.…”
Section: Discussionsupporting
confidence: 47%
“…Thus, the adhesin binding site on DAF is similar, but distinct, for the four adhesins of the Dr adhesin family, and involves SCR3 as well as SCR2 in some cases . We had investigated previously a rare polymorphism of human DAF, designated Dr(a-), and we found that it arose from a point mutation that changed a single amino acid in SCR3: Sertbs i n the high-frequency Dr-allele to Leu in the rare Drb [Dr(a-)] allele (30). We also found that erythrocytes of the Drb phenotype did not bind Dr adhesin (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical pathway convertase and the Dr adhesin-binding regions are both localized on the SCR-2-SCR-3 interface of DAF, suggesting a possible overlap of binding regions. A rare polymorphism of human DAF containing a point mutation in SCR-3 (Ser165-Leu) (32,39), designated Dr(a Ϫ ), abolishes binding of Dr adhesins (40).…”
mentioning
confidence: 99%
“…The very rare Dr(a–) phenotype is a partial DAF deficiency phenotype as a result of alternative splicing of DAF mRNA. Despite the reduced DAF expression, Dr(a–) erythrocytes function normally in the complement lysis sensitivity assay [6]. The inherited Dr(a–) phenotype has been found in Israel only in 4 families who immigrated from the area of Bukhara [7, 8].…”
Section: Discussionmentioning
confidence: 99%